Assessment of energy performance certificate systems: a case study for residential buildings in Turkey - Yigit, Kenan; Acarkan, Bora (Tubitak Scientific & Technological Research Council Turkey, 2016)
The importance of sustainable development and energy efficiency efforts has increased in the construction sector. Energy-saving efforts for buildings have become more important due to the global energy crisis, and energy rating systems have been developed globally for assessment of energy performance. In this study, international green building certificate and energy performance certificate (EPC) systems are presented. The official EPC system for buildings in Turkey is illustrated with case studies. Energy consumption and greenhouse gas emissions from residential buildings are calculated using the official national software, which is called BEP-TR. The impact of lighting on the total energy performance of residential buildings is also examined. Changes in energy performance values are discussed for various cases. As a result of this study, it was determined that residential buildings constructed before 2000 consume more energy than those constructed after 2000; they are a lower energy performance class of buildings. Use of energy-saving lamps has also had a positive impact on both lighting and total energy performance classes. This paper aims to contribute to the promotion of building energy certification systems and energy efficiency issues for the construction sector.
Keywords: Building; energy performance certificate; lighting; energy efficiency; OFFICE BUILDINGS; LEED; PERSPECTIVES; CONSUMPTION; PROJECTS; EFFICACY; Computer Science; Engineering